Validation of the Viral Load Testing Criteria - an algorithm for targeted viral load testing in HIV-positive adults receiving antiretroviral therapy. - Thorman, Johannes; Björkman, Per; Tesfaye, Fregenet; Jeylan, Asiya; Balcha, Taye Tolera; Reepalu, Anton (Tropical Medicine & International Health, 2019)
Objectives: Restricted capacity for viral load (VL) testing is a major obstacle for antiretroviral therapy (ART) programmes in high-burden regions. Algorithms for targeted VL testing could help allocate laboratory resources rationally. We validated the performance of the Viral Load Testing Criteria (VLTC), an algorithm with satisfactory performance in derivation (sensitivity 91%, specificity 43%).Methods: HIV-positive adults who had been receiving first-line ART for ≥12 months at three Ethiopian public ART clinics were included. Healthcare providers collected data on variables of the VLTC: current CD4 count, mid-upper arm circumference (MUAC) and self-reported treatment interruption. VL testing was performed in parallel. Performance of the algorithm for identification of patients with VL ≥ 1000 copies/ml was evaluated.Results: Of 562 patients (female 62%, median ART duration 92 months), 33 (6%) had VL ≥ 1000 copies/ml. Sensitivity for the VLTC was 85% (95% CI, 68-95), specificity 60% (95% CI, 55-64), positive predictive value 12% (95% CI, 10-14) and negative predictive value 98% (95% CI, 97-99). Use of the algorithm would reduce the number of VL tests required by 57%. Misclassification occurred in 5/33 (15%) of subjects with VL ≥ 1000 copies/ml.Conclusion: In validation, the VLTC performed similarly well as derivation. Use of the VLTC may be considered for targeted VL testing for ART monitoring in high-burden regions.